Pengaruh Social Media Tiktok Terhadap Minat Beli Konsumen Pada Brand Akun @aerostreet - Alamsyah, Ramadhani; Ismail, Oki Achmad (eProceedings of Management, 2024)
Business in Indonesia, especially the fashion sector, is growing rapidly with increasingly fiercecompetition, encouraging managers to move forward and meet market needs. Business success dependsnot only on profits, but also on effective promotion and understanding consumer needs. Social media isbecoming an important tool in marketing, with April 2023 data showing 61% of Indonesia's populationuses online entertainment. Platforms like TikTok, with user engagement of 70.8%, offer greatopportunities for product promotion. The COVID-19 pandemic accelerated the shift to online shopping,increasing digital transactions by 300%. TikTok, popular among the younger generation, plays animportant role in digital marketing and influences consumer behavior with features such as the yellowbasket. This research uses a quantitative method based on positivism, descriptive in nature with a causalcorrelation method to analyze the relationship between the independent variable (TikTok) and thedependent variable (Purchase interest). The normality test results show that the data can be used becausethe residuals are normally distributed. Social media is effective for marketing due to its widespread andregular use, facilitating the online purchasing experience. TikTok, with its short video duration, createsinterest in the audience, encouraging them to search for more information about the product. Researchshows that TikTok has a moderate relationship to Aero Street buying interest, with a 1% increase in TikTokincreasing buying interest by 0.468. Statistical tests show a significant influence of TikTok on purchaseintention with a coefficient of determination of 35.1%, while 64.9% is influenced by other variables not discussed. TikTok social media has a positive and significant relationship with purchasing interest, withthe entertainment dimension having an influence of 83.2% and exploration interest 79.6%. Keywords-Tiktok, interest in buying, Aerostreet.